Sistem Informasi Penjualan Sparepart di Bengkel Karisma Motor Berbasis Web - Junius Effendi, Muhammad; heriansyah; Fransiska, Welly (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya, 2024)
Technological developments continue to grow rapidly and touch all aspects of life. Companies from small to large scale take advantage of technological developments to increase company value, one of the most commonly heard of technological developments is the internet. The internet is a major requirement in this globalization era, with the internet we can get any information, including information about schools, hospitals and even workshops [1]. speartpart sales and other materials needed. In the face of very tight workshop competition at this time and in the future. However, currently there are still many workshops that have not utilized internet technology, one of which is the Karisma Motor workshop in Muara Pinang. This research will be built using the Prototype method.